Music Intervention to Reduce Anxiety in High-Risk Group of Stroke in Puskesmas Banjar Serasan - Safitri, Dewin; Arisandi, Defa; Nurpratiwi, Nurpratiwi; Rusdian Hidayat, Uti; Akbar, Ali; Alfikrie, Fauzan; Amaludin, Mimi; Hatmalyakin, Debby (Jurnal Keperawatan Profesional (KEPO), 2025)
Stroke is the second leading cause of death and a major source of disability worldwide. Hypertension and diabetes mellitus are major risk factors for stroke. Anxiety can worsen the condition of patients with hypertension and diabetes mellitus, which can increase the risk of stroke. Music intervention is one of the non-pharmacological measures that can reduce anxiety. This study aimed to analyze the effect of music intervention on anxiety in high risk stroke groups in the Banjar Serasan Health Center working area. The research design used was pretest posttest without control group. The population in this study consisted of patients with hypertension and diabetes mellitus at Banjar Serasan Health Center. The sample size was 30 subjects Hamilton Anxiety Rating Scale (HARS) instrument consisting of 14 statements was used to measure anxiety. Bivariate analysis was concted using a paired t-test. The results showed a p-value of 0,000 which indicated that there was an effect of music intervention on anxiety in the high risk stroke group. Music intervention affected anxiety in high risk stroke group. Patients with hypertension and diabetes mellitus as a high risk group for stroke are advised to keep doing music intervention independently to control anxiety.